Peningkatan Keterampilan Komunikasi Pelayanan Publik Bagi Tenaga Kesehatan : Studi Kasus pada Puskesmas Petir Kota Tangerang - Muhammad Didi Ahmadi (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to explore the communication styles and experiences of healthcare workers in enhancing public service communication skills at Petir Community Health Center (Puskesmas Petir) in Tangerang City. Effective communication is a crucial factor in the quality of healthcare services for patients; however, various challenges such as time constraints, differences in patients’ backgrounds, and work pressure often hinder optimal interactions. This research employs a qualitative approach with a case study method, involving in-depth interviews, participatory observations, and document analysis to uncover the experiences, perceptions, and practices of healthcare workers in communicating with patients and the community. The findings indicate that communication skills are improved through internal training, peer mentoring, and the adaptation of communication strategies to match patient characteristics. Additionally, personal motivation, managerial support, and a conducive work environment play significant roles in the successful implementation of communication strategies. The results of this study provide an in-depth understanding of public service communication practices within the community health center context and serve as a basis for recommendations in developing training programs and policies to enhance the quality of interactions between healthcare workers and the community.